Bioeconomic models and agroforestry policy analysis applications to silvopastoral systems in Guanacaste, Costa Rica - Monterroso Rivas, Adolfo O. (CATIE, Turrialba (Costa Rica), 2014)
Tesis (Ph.D.) - CATIE, Turrialba (Costa Rica), 2005